(untitled) (Fiep Bulletin - online, 2016)
This article is a result of bibliographic research whose proposal suggests the use of football as a sport facilitator initial motor and cognitive development of children of school age. Including because it is a national passion for sport and easy access to your practice, you can use this factor as an aid in motor and cognitive practices thus arousing interest in healthy sports practice , reinforcing and contributing in motor memory to practitioners mode .